Contextual Cueing Effect in Spatial Layout Defined by Binocular Disparity - Zhao, Guang; Zhuang, Qian; Ma, Jie; Tu, Shen; Liu, Qiang; Sun, Hong-jin (Frontiers in Psychology, 2017)
Repeated visual context induces higher search efficiency, revealing a contextual cueing effect, which depends on the association between the target and its visual context. In this study, participants performed a visual search task where search items were presented with depth information defined by binocular disparity. When the 3-dimensional (3D) configurations were repeated over blocks, the contextual cueing effect was obtained (Experiment 1). When depth information was in chaos over repeated configurations, visual search was not facilitated and the contextual cueing effect largely crippled (Experiment 2). However, when we made the search items within a tiny random displacement in the 2-dimentional(2D) plane but maintained the depth information constant, the contextual cueing was preserved (Experiment 3). We concluded that the contextual cueing effect was robust in the context provided by 3D space with stereoscopic information, and more importantly, the visual system prioritized stereoscopic information in learning of spatial information when depth information was available.